Pengaruh Pengembangan Sumber Daya Manusia Terhadap Kinerja Pegawai Kantor Kecamatan Sajoanging Kabupaten Wajo - Ainul Fitriani; Yuniarni Yusuf; Eka Patmasari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Human resource development is a vital activity that organizations must undertake to ensure that employees' knowledge, talents, and skills align with job requirements. Measuring the quantity of work completed by employees within a specific time frame using tools tailored to the nature of their work is referred to as employee performance. This study aims to determine the extent of the influence of human resource development on employee performance at the Sajoanging Sub-district Office, Wajo Regency. The theoretical framework for this research includes: Variable X (Human Resource Development) as defined by Nugraha (2016:178), encompassing education, work experience, skills, and technological capabilities. Variable Y (Employee Performance) as defined by Dewi & Harjoyo (2019:80), including work results, job knowledge, time discipline, reliability, and attitude. This research employs a census approach, meaning questionnaires are used to gather information from the entire population. The sample size for this study consists of 18 individuals. Data collection methods include questionnaires and observation. Quantitative associative analysis and descriptive data analysis are employed for data processing. The findings reveal that: Human resource development at the Sajoanging Sub-district Office, Wajo Regency, falls within the